2008
DOI: 10.1016/j.vaccine.2008.04.080
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based vaccines protect against zoonotic schistosomiasis in water buffalo

Abstract: Schistosomiasis japonica is an endemic, zoonotic disease of major public health importance in China where water buffaloes account for approximately 75% of disease transmission. Interventions that reduce schistosome infection in water buffaloes will enhance their health simultaneously reducing disease transmission to humans. While chemotherapy has proved successful, it requires continued time consuming and expensive mass treatments. A more sustainable option would be development of vaccines that reduce transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
125
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 59 publications
(94 reference statements)
5
125
1
Order By: Relevance
“…Members of the tetraspanin family from different organisms are structurally and functionally related [18,31]. Phylogenetic analysis indicated that TSP2 of E. multilocularis is phylogenetically related to TSP2 [15], Sm23 [20] and SJC23 [21,22] of Schistosoma, the protective antigens against schistosomiasis, while TSP5 is closely related to the T24 antigen of T. solium, a diagnostic antigen for cysticercosis [26]. We suppose that among these proteins, some may be vaccine candidates, while others may be useful as diagnostic antigens.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Members of the tetraspanin family from different organisms are structurally and functionally related [18,31]. Phylogenetic analysis indicated that TSP2 of E. multilocularis is phylogenetically related to TSP2 [15], Sm23 [20] and SJC23 [21,22] of Schistosoma, the protective antigens against schistosomiasis, while TSP5 is closely related to the T24 antigen of T. solium, a diagnostic antigen for cysticercosis [26]. We suppose that among these proteins, some may be vaccine candidates, while others may be useful as diagnostic antigens.…”
Section: Discussionmentioning
confidence: 95%
“…Although some tetraspanins have been demonstrated to be potential vaccine candidates against different stages of schistosome infection [19][20][21][22], nothing is known about them in another important platyhelminth E. multilocularis. Recently, many studies have focused on the LEL domain of tetraspanin because of its important functions in mediating protein-protein interactions and homodimerization [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations